Pemanfaatan Internet of Things dalam Bidang Agrikultur: Literatur Review - Rifky Ramadhan; Rabiul Iman Khatami; Muhammad Rafli Maulidri; Nur` Ain; Muh Rezky. S (Program Studi Bisnis Digital, Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sidenreng Rappang, 2025)
The Internet of Things (IoT) has become a key technology in the transformation of the agricultural sector towards smart and sustainable agriculture. Through a review of various studies in the past decade, this study reveals that the implementation of IoT in irrigation systems, environmental monitoring, and real-time crop management has improved resource efficiency and productivity of agricultural products. This paper aims to systematically examine the application of IoT technology in the agricultural sector over the past decade (2015–2025), with a focus on efficiency, sustainability, and digital transformation in agriculture. This study aims to identify research trends, technology applications, implementation challenges, and innovative solutions developed by researchers in supporting smart agriculture and food security. The research method used was in the form of a systematic literature study. The results of the study show that IoTenables automation, remote monitoring, and data-driven decision-making, although challenges still exist in terms of technology access, cost, and system security. Overall, the application of IoT in agriculture not only improves technical efficiency, but also makes a significant contribution to the achievement of sustainable agriculture and food security amid the challenges of climate change.